2019
DOI: 10.1007/s40071-019-0227-8
|View full text |Cite
|
Sign up to set email alerts
|

Sponge-associated fungi from a mangrove habitat in Indonesia: species composition, antimicrobial activity, enzyme screening and bioactive profiling

Abstract: There is no report of diversity, biological properties and bioactive compounds of sponge-associated fungi from Indonesia's mangrove ecosystem to date. This study was designed to isolate sponge-associated fungi from a mangrove ecosystem in Mangkang, to screen the antimicrobial and extracellular enzyme properties of the isolates, characterize the biologically promising isolates using molecular approaches, and profile the secondary metabolites using phytochemical and thin-layer chromatography (TLC) analyses. An u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
0
29
0
2
Order By: Relevance
“…Both pigment types have significant antimicrobial and antioxidant properties [ 6 , 19 , 43 , 44 ]. Yellow pigments of haloarchaea are compounds such as 4,4’-diaponeurosporene, zeaxanthin, or lutein with applications in food colorants, visual acuity, and antibacterial activity against multidrug-resistant organisms [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both pigment types have significant antimicrobial and antioxidant properties [ 6 , 19 , 43 , 44 ]. Yellow pigments of haloarchaea are compounds such as 4,4’-diaponeurosporene, zeaxanthin, or lutein with applications in food colorants, visual acuity, and antibacterial activity against multidrug-resistant organisms [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chrysoporthe sp. exhibited strong antibacterial activity against E. coli and S. aureus (Nirma et al, 2015); and Fusarium species produced metabolites with activities against microbial pathogens (Sibero et al, 2019). Besides, from F. larvarum, an antifungal compound active against C. albicans and a wide range of pathogenic fungi was isolated, called Parafungin (Harvey et al, 2015).…”
Section: Fungal Strain Code Labmicramentioning
confidence: 99%
“…Our previous research also showed that spongeassociated fungi have several bioactivities such as anti-S. aureus and E. coli (Wittriansyah et al 2016), antibacterial produced by sponge Agelas sp. associated fungi Fusarium solani , and Sibero (2019) has also reported that sponge-associated fungi from a mangrove habitat were producing anti-microbial activities.…”
Section: Introductionmentioning
confidence: 99%